Market Share and Profitability: The Case of the Philippine Commercial Banks - Patalinghug, Epictetus E. (Philippine Management Review; Vol 1 (1990), 2016)
This paper attempts mainly to substantiate the hypothesis that market share and profitability are positively correlated.  An examination of data from the Philippine commercial banking industry confirmed the positive link between market share and profitability, although the impact of the Philippine National Bank (PNB) distorted the relationship presumably because PNB may have been operating beyond the most efficient scale during the period examined.